Intra-peritoneal adhesion in rabbit - KONWAR, B; SAIKIA, B; SHARMA, K (The Indian Journal of Animal Sciences, 2011)
Intra-peritoneal adhesion and their treatm.ent were evaluated in 4 groups of 8 rabbits each. The group A was treated as control and group B, C andÂ·D were treated with placentrex, povidone iodine and human amnioticmernbrane respectively. The mean total protein, nucleated cell count and neurtophil were significantly increased in peritoneal fluids of group A, whereas Inacrophage count increased in all the groups. Intra-peritoneal administrations of povidone iodine to serosal cuts at uterus and stomach in rabbits were luuch more effective in preventing intra-abdominal adhesion formation after surgical manipulation than the placentrex and human amniotic membrane. Â